2017
DOI: 10.1155/2017/2805370
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acute Toluene Toxicity on Different Regions of Rabbit Brain

Abstract: The acute phase effects of toluene on the brain have been investigated in this study using rabbit brain via histopathological, immunohistochemical, and biochemical methods. A total of 20 male rabbits were used as control and experimental groups. Moreover, nerve growth factor (NGF), tumor necrosis factor-alpha (TNF-alpha), dopamine (DA), and glial fibrillary acidic protein (GFAP) tests were performed in order to designate the severity of the biochemical damage. In the biochemical evaluation of the prefrontal co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 23 publications
3
19
0
Order By: Relevance
“…Tas et al (2012) reported that exposure to the high dose of toluene (5200 mg/kg/gavage) for 2 weeks caused a significant increase in the immune reactivity of Bax in the cerebellum and the brain cortex (Tas et al, 2012). Demır et al (2017) demonstrated that acute exposure to toluene by a single dose (876 mg/kg) intraperitoneal (IP) injection in the New Zealand rabbits brain caused significantly extreme expansion of the blood vessels, dispersed cell borders, vacuolar degeneration, severe degeneration of the compensation, perivascular demyelination, gliosis, and several necrosis and pyknotic cells (Demır et al, 2017). Moreover, a noticeable enhance in the count of apoptotic cells in the cerebral granule layer was indicated by inhaling 1200-1800 ppm toluene for 6 h per day in rats (Dalgaard et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tas et al (2012) reported that exposure to the high dose of toluene (5200 mg/kg/gavage) for 2 weeks caused a significant increase in the immune reactivity of Bax in the cerebellum and the brain cortex (Tas et al, 2012). Demır et al (2017) demonstrated that acute exposure to toluene by a single dose (876 mg/kg) intraperitoneal (IP) injection in the New Zealand rabbits brain caused significantly extreme expansion of the blood vessels, dispersed cell borders, vacuolar degeneration, severe degeneration of the compensation, perivascular demyelination, gliosis, and several necrosis and pyknotic cells (Demır et al, 2017). Moreover, a noticeable enhance in the count of apoptotic cells in the cerebral granule layer was indicated by inhaling 1200-1800 ppm toluene for 6 h per day in rats (Dalgaard et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Noise and toluene are some of the prevalent physical and chemical stressors in different workplaces. Previous studies have indicated that different stressors could deteriorate some brain disorders (Demır et al, 2017;Xiu et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…[ 33 ] Increased Bax protein, a proapoptotic protein from the mediator's apoptosis, increases apoptosis. [ 34 ] A study reported increased Bax expression in relation to diffuse alveolar damage. A sepsis‐induced polymicrobial septic rat model found a link between activation of apoptotic cascades and increased pulmonary edema during the progression of sepsis in lung tissue.…”
Section: Discussionmentioning
confidence: 99%
“…This can affect the life expectancy of a person to be lower. Thus, companies are required to carry out periodic checks so that dangerous diseases can be prevented as early as possible (Reid et al, 2012;Jonathan Posner, James A. Russell, 2014;Demir et al, 2017).…”
Section: Discussionmentioning
confidence: 99%